VD_FINDINFO Jug / 2013 / 33 vom 30. Mai 2011 - VD Tribunal cantonal (2011)
PARTIE CIVILE, FRAIS DE LA PROCÉDURE, DÉPENS | 423 CO, 150bis CP, 2 LCD, 126 CPP (CH), 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 433 al. 1 CPP(CH)